Intraluminal mucus cast complicating carcinoma of the colon. Issue 733 (November 1986) - Chapple, C. R.; Shah, V. M.; Newman, J.
Abstract : A previously unreported complication of a stenosing carcinoma of the colon is described. This was first noticed as a rather unusual X-ray appearance, the significance of which only became clear following surgery.